LEARN TO TEACH WRITING THROUGH WRITING - Svetlana Suchkova; Gulnara Dudnikova (English Review: Journal of English Education, 2013)
Abstract: This paper discusses some major issues concerning teaching writing to future teachers. There are a lot of EFL/ESL textbooks focused on teaching writing. However, those that are intended for trainee teachers are rare on the market. The goal of this paper is to share the result of several years of work on the writing syllabus and materials that is effective in the process of teaching future teachers. It contains sample of tasks based on certain principles that may promote teachers to become effective writers for themselves and, at the same time, to acquire initial professional skills necessary in their future career. A course book can not address any audience in general. It must focus on a particular learner, the objectives, and content of the process of learning. In the situation when no textbook meets these requirements, the problem of providing students with an appropriate textbook must be solved by creating new textbooks. Keywords: writing skills, strategies, professional needs, syllabus, teaching/learning materials.Â